Estudo da reação de Knoevenagel em condições eco-amigáveis visando às sínteses de compostos carbonílicos α,β- insaturados e cumarinas - Ferreira, João Marcos Gomes de Oliveira (2021)
Knoevenagel condensation is of great importance in organic synthesis. With the growing concern with clean methodologies, new protocols for its execution have been sought. This study looks at the applicability of the binary ethanol: water mixture in the synthesis of Knoevenagel adducts with ketones, in sequential reactions in the synthesis of coumarins and associated with Lewis acid type catalysts. When the binary ethanol: water (3: 7) system was applied to the synthesis of isatin-derived Knoevenagel adducts, the effectiveness of the methodology was confirmed, corroborated by the good times (1.5 to 7.5 hours) and yields (79 to 96%). When the same system was applied in the synthesis of coumarins from salicylaldehydes, it was noticeable that the elimination step, after cyclization, is influential in the reaction speed; with methyl cyanoacetate being the best compound with active methylene. Altogether 9 coumarins were synthesized, between 1.16 to 3.50 hours, with yields of 72 to 99%. The adducts derived from isatin and coumarins synthesized were submitted to the Swiss ADME. As pharmacokinetic data, all showed passivity of absorption by the gastrointestinal tract, in addition to not being substrates of P-Gp. However, among them, only four adducts and four coumarins, exhibited potential passive permeation through the blood-brain barrier. In the optimization of the reaction aiming at the synthesis of adducts at room temperature, the NaCl salt was the most effective of the catalysts tested in the synthesis of Knoevenagel adducts synthesized from aromatic aldehydes and malononitrile, requiring 2 to 75 minutes, obtaining yields between 83 % and 97%. This new methodology is an ecologically correct synthesis protocol due to the low toxicity of the solvents and catalyst used; operation at room temperature and ease of isolation of products as they precipitate in the reaction medium. Tests were carried out in multicomponent reactions of the Biginelli type and synthesis of 4H-pyranes, however we concluded that only the solvent systems and catalysis with a Lewis acid with low coordination number, such as the Na+ ion, are not sufficient to promote these multicomponent reactions, being the subject of future studies.